Enhancing Students’ Learning Outcomes through Think-Pair-Share Strategy Integrated with Card Sort in Learning Islamic Inheritance Mathematics - Septiawan, Fanni; Zuhriawan, M. Qoyum (Journal of the Indonesian Mathematics Education Society, 2025)
Islamic education knows a lot of mathematics that is delivered to students, one of which is related to the rules of human life, namely fiqh, and fiqh is also known as boring mathematics if the delivery is not pleasant from the teacher. From these problems, the researcher will discuss the learning process and learning outcomes of students using think pair share with the help of card sort. The purpose of this study is to determine the improvement of student learning outcomes in fiqh lessons of Mawaris mathematics by using card sort-assisted think pair share learning. The research method used in this study is qualitative research using a descriptive approach. The place of this research is at MA Ma'arif 14 Sukorame Lamongan. The main source of data in this study is teachers, fiqh teachers, students. The results of this study show that the use of card sort media in teaching can make students more involved and active in the learning process, so that they are more active in discussing and generating ideas. The use of the card sort-assisted Think Pair Share method also provides a clearer understanding of the mathematics, and a more effective learning strategy. This approach can be adapted to a variety of learning models, allowing learners to learn more effectively and efficiently. Using the card sort-assisted Think Pair Share method in Mawaris lessons can improve students' learning experiences and encourage creativity.